Analysis of Consumer Profiles and Factors Affecting the Intention to Shop Online During the COVID-19 Pandemic Using the Technology Acceptance Model - Fida Ghazy Istikomah (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
The Covid 19 pandemic has significantly transformed consumer shopping behavior by limiting face-to-face interactions. This study examines the effects of perceived ease of use, perceived usefulness, perceived enjoyment, perceived compatibility, and perceived social pressure on online shopping intentions during the pandemic while also profiling consumers who increased their online shopping activity. A total of 300 respondents in Yogyakarta who shopped online during Covid 19 were surveyed using purposive sampling. A quantitative approach was applied with primary data collected through structured questionnaires. Data were analyzed using descriptive statistics, factor analysis, and multiple linear regression in SPSS. Results show that all five factors, ease of use, usefulness, enjoyment, compatibility, and social pressure, positively and significantly influence online shopping intentions. The findings offer practical insights for e commerce strategies and consumer engagement during crisis periods.